Resource Exploitation of Developing Countries Under the Guise of Neoliberalism (Philosophy and Progress, 2025)
Since the 1970s, a transformative trend in global trade policy began to emerge, characterised by the strategic relocation of industries, particularly those detrimental in several respects, most notably within the environmental context, from economically advanced nations to less developed ones. This trend necessitates the transfer of resource-extracting industries (REIs) to continue their extraction activities in emerging nations, purportedly justified by these countries’ enhanced capabilities in resource management and extraction. However, a thorough examination of the extraction practices of these REIs reveals that numerous ethical dilemmas remain unresolved.This article endeavours to critically assess the practices of REIs based in developed countries that extract significant resources, such as cobalt and oil, from developing countries. I will demonstrate that the resource extraction processes of REIs in these nations blatantly contravene established norms pertaining to human and environmental rights, resulting in a profound manifestation of injustice termed exploitation. Affluent REIs conduct such exploitative extractions by adhering to neoliberal ideologies that predominantly serve their own interests over those of the host developing states. By embedding neoliberal ideology into their expansive trade strategies, REIs have effectively established a form of corporate imperialism that adversely impacts socio-economic conditions in developing countries. Consequently, neoliberalism emerges as a political ideology that fosters exploitation and rights violations, enabling REIs to secure financial gains at the expense of developing nations. Therefore, it is advised that resource-rich developing nations either eschew the integration of neoliberalism into their mineral policy frameworks or, if integration is considered essential, approach such incorporation with meticulous care while ensuring the protection of the rights of the working populace and the preservation of the environmental sanctity.Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 167-189